The Roaring Meeting Leontiev, Rozanov and Russian Modernism: The Aesthetic Method Transformation - Sarychev, Yaroslav (Opción, 2019)
The article deals with the problem of the influence of Leontiev’s aesthetic doctrine on a certain modernistic literature branch, known as new religious consciousness or Neo-Christianity via comparative qualitative research methods. As a result, the conducted analysis also allows insisting on the historical and epistemological adjustment of the existing approaches to a number of phenomena in Russian literature and philosophy of the latter third part of the 19th– early 20th centuries. In conclusion, the main achievement of this article is the discussion of the practically unexplored problem of the genesis of original national characteristic features of Russian modernism.